Linking functional responses and effects with stoichiometric traits - Eric K. Moody; Katie Anania; Kate S. Boersma; Tyler J. Butts; Jessica R. Corman; Spencer Cruz; W. Reilly Farrell; Kauan N. Fonseca; Amy C. Krist; Erin I. Larson; Alex Lewanski; Christian Liriano; et al. (Ecology, 2025)
Trait‐based approaches to study biodiversity responses to changing environmental conditions have become popular because these approaches provide context to how and why certain taxa shift in abundance within an assemblage. Trait‐based approaches also offer the potential to link shifts in assemblage composition to effects on ecosystem functions like rates of primary production, detrital decomposition, and nutrient uptake. However, focusing on response traits in multidimensional functional diversity studies limits our ability to make these linkages. We developed a multidimensional analytical and visual stoichiometric diversity framework that links organismal responses to and effects on environmental change using stoichiometric traits. We define these traits as the acquisition, assimilation, allocation, and excretion of key chemical elements by members of an assemblage. We discuss the considerations for using stoichiometric traits in a trait‐based framework and apply the framework to case studies of temporal variation in stream benthic invertebrate assemblages and spatial variation in urban woody vegetation assemblages. These examples illustrate the utility of the stoichiometric diversity framework for testing stoichiometric hypotheses and suggest promising linkages between assemblage shifts and shifts in ecosystem function.